Moving the British National Collections - Foot, Mirjam M. (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2000)
There is no point in rehearsing the lengthy saga of building the new British Library in North London. The media made much of it − much of it inaccurate − and the Library, its staff and its users are now only too pleased to put all that behind and are eager to work in and with the new building, enjoying its amenities and much improved services. However, between the actual building of the new library and its enjoyment lies an important interlude, which has been discussed far less − at least in public and by the press − and that is the gigantic effort of moving 250 kilometres of library and archive material from ten different locations into the new and vastly improved storage areas at St Pancras. As an introduction to this panel discussion I will highlight four issues, the details of which will − I hope − be developed further when the introductions are over and the discussion starts. They are: 1. Planning and budgets, 2. Diversity of collections and locations, 3. Preservation and security, and 4. Lessons learnt.